Problem Solving Skills based on IDEAL Model in Implementing Undergraduate Final Year Project - Gusau, Muhammad Baba; Nabila, Nabila; Md Som, Mohamad; Mohamad, Mimi Mohaffyza (Kolej Komuniti Sungai Siput Perak, 2020)
Problem solving skills is the formal framework for undergraduate program in science and technical knowledge. This work aims to define the problem skills of the final year project (FYP) students. Most educators believe that problem solving is among the most important and practical kinds of learning and thought. One of the approach of problem solving skills introduced by Brandsford in IDEAL Model. This model consists five stages of problem solving; identify problem as opportunities, define the problems, develop and understanding goals, explore possible strategies, anticipate potential effects before apply and look back and learn. This research objectives are to develop research instrument based on IDEAL Model and identifying problem solving skills among students in conducting FYP. There are 324 students involved in this research from eight faculties in Universiti Tun Hussein Onn Malaysia. The findings indicate that the reliability of the research instrument is sufficient to use and that the mean of identifying problem as opportunities in the IDEAL model showed higher score than other approaches. To sum up, problem-solving receives considerable attention in the undergraduate and helps students to improve their academic and problem-solving skills. Research on the development of problem-solving skills by students, the transfer of problem-solving skills to new contexts, and the effectiveness of particular pedagogical approaches to problem-solving teaching has provided a basis for academically accomplishments by students.